ANALISIS KEBUTUHAN TENAGA KERJA MENURUT ABK-KES PADA UNIT FILING DI UOBK RSUD DOKTER MOHAMAD SALEH PROBOLINGGO - Chyntia Vicky Alvionita; Fresvian Jenrivo (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2023)
The administration of Medical Records must be supported by qualified, experienced human resources and a workload that is appropriate for the officers who are on hand. The UOBK RSUD Dr. Mohamad Saleh Probolinggo has four filing officers, one of whom has a bachelor's degree in economics and the other three have only completed high school. The purpose of this study is to analyze the workload of filing officers and calculate the need for labor in the filing unit. This type of research is descriptive qualitative with data collection methods through interviews and observations. Calculations made with ABK Kes produced data on the requirement for 12 health human resources, resulting in the demand for 8 more staff in the filing unit.